Dexmedetomidine Continuous Infusion for Refractory Cancer Pain at End of Life: A Case Report. (3rd July 2022) - Byrne, Jennifer M.; Mesarwi, Paula; Edmonds, Kyle P.; Atayee, Rabia S.
Abstract: Refractory cancer-related pain at end-of-life (EoL) is multifaceted and may require utilizing medications with different mechanism of actions beyond opioids. We report the successful use of dexmedetomidine in a 63-year old female with recurrent breast cancer and intractable left arm pain and swelling admitted to University of California, San Diego, Health (UC San Diego Health), palliative care unit. Patient's pain and agitation continued to persist and she declined clinically despite efforts to start methadone, continuous infusion opioids, continuous infusion lidocaine and intravenous chlorpromazine by the palliative care team. On hospital day (HD) 11 patient was started on dexmedetomidine continuous infusion for refractory pain per our protocol at UC San Diego Health. The next day the patient appeared much improved in terms of pain and agitation with grimacing and moaning completely resolved. She was able to have some lucid periods and interacting with her family. With the addition of dexmedetomidine to her pain regiment, the patient was able to peacefully die 5 days later. This case report highlights the clinical utility of demedetomidine in a palliative care unit for refractory pain at EoL.